Penguatan Peran Sektor Perbankan dalam Mendukung Pemulihan Ekonomi Pasca Pandemi - Badzlina, Ghassani; Emiarti, Endah (ITB AAS INDONESIA Surakarta, 2025)
The banking sector plays a crucial role in accelerating economic recovery post-COVID-19. This study aims to analyze the impact of banking policies, digital transformation, and Islamic banking contributions in supporting economic recovery. Using a qualitative approach with a literature review method, this research examines various financial policies, technological advancements, and alternative financing mechanisms within the banking sector. The findings indicate that flexible credit policies, digital banking adoption, and the growth of Islamic banking significantly contribute to economic resilience. Credit restructuring and government-backed financing programs have supported micro, small, and medium enterprises (MSMEs), enabling them to sustain operations amid financial challenges. Digital banking transformation has expanded financial access, improved transaction efficiency, and reduced reliance on traditional banking services. Meanwhile, the increasing acceptance of Islamic banking reflects a growing preference for sustainable and ethical financial systems. This study provides new insights by linking banking policies with digitalization trends and the role of Islamic banking in post-pandemic economic recovery. Further research should focus on evaluating the long-term impact of digital banking on consumer behavior and the role of financial technology in fostering economic resilience.